Advances in adaptive computational methods in mechanics - Ladeveze, Pierre, 1945- (Studies in applied mechanics)
Mastering modelling, and in particular numerical models, is becoming a crucial and central question in modern computational mechanics. Various tools, able to quantify the quality of a model with regard to another one taken as the reference, have been derived. Applied to computational strategies, these tools lead to new computational methods which are called "adaptive". The present book is concerned with outlining the state of the art and the latest advances in both these important areas. Papers are selected from a Workshop (Cachan 17-19 September 1997) which is the third of a series.